تقنية إضافة عناصر جديدة إلى قاعدة بيانات برنامج Multisim - فاروسي فاتن (Latakia University Journal -Engineering Sciences Series, 2017)
يهدف البحث إلى دراسة كيفية إضافة عناصر جديدة إلى قاعدة بيانات برنامج Multisim أو كيفية نمذجة عنصر باستخدام اللغة البرمجية C++ من أجل استخدام هذا العنصر فيما بعد في تصميم وتركيب الدارات والأجهزة الالكترونية. تحتوي قاعدة بيانات Multisim نماذج مدمجة لأغلب الأجهزة الالكترونية، وتهدف الدراسة إلى وضع أسس وطريقة لنمذجة العناصر الالكترونية غير الموجودة ضمن قاعدة بيانات برنامج Multisim ( أو موجودة وبقيم مغايرة), والتي نحتاجها أثناء استخدام هذا البرنامج في عملية النمذجة والمحاكاة لدارة ما. وقد تم اقتراح أسلوب نمذجة الشيفرة Code modeling للوصول إلى هذا الهدف, ويعتمد هذا الأسلوب على سلوك الجهاز أو العنصر المنمذج. وتبين الدراسة كيفية إنشاء نموذج شيفرة Code model لمكثف بقيم محددة ومغايرة للموجودة ضمن قاعدة البيانات وإضافته إليها. The research aims to study how to add new components to Multisim database. Or how to model a component using the programing language C++ , to use this new component later in designing and making electronic circuits and devices. Multisim has built-in models for most types of devices, , the study aims to lay the foundations and method for modeling of electronic items which is not located within the Multisim program database, (or present with different values) , and that we need while using this program in the modeling and simulation process for a given circuit. Code modeling method has been proposed to reach this goal; this method relies on the behavior of the device or the modeled component. The study shows how to create a Code model for a specific capacitor that has different values to those existing within the database and add to it.